Phylogenetic Relationships in the Genus Paspalum (Poaceae: Panicoideae: Paniceae): An Assessment of the Quadrifaria and Virgata Informal Groups - Giussani, Liliana Mónica (2009)
Paspalum, an American genus of the x = 10 Paniceae clade, includes about 330 species, four subgenera, and 27 informal groups. Within the genus, the Quadrifaria and Virgata groups are well-represented in South and Central America. Interspecific variability make the delimitation of these groups difficult; hence several species have been included or excluded from Quadrifaria or Virgata depending on the taxonomic treatment. In previous analyses, the Quadrifaria and Virgata groups of Paspalum were polyphyletic. Here we present a new appraisal of the classification of both groups based on the phylogenetic analyses of DNA data from the chloroplast: the rpl16 intron, and the region comprising the trnL and trnF genes. A monophyletic Virgata clade is recovered, consisting of nearly all the species listed in an unpublished manuscript. The Quadrifaria group is restricted to P. quadrifarium and P. quarinii. Other clades grouped species traditionally treated within Virgata or Quadrifaria, although their phylogenetic placement needs to be reevaluated. Within most of the clades, diploid and polyploid species seemingly derive from a common ancestor denoting an autopolyploid origin. Alloploidy is also possible although reticulate evolution needs to be explored. The wide distribution of the I genome suggests that this is a plesiomorphic state in Paspalum.